Long-term impact of war on healthcare costs: an eight-country study - Sabes-Figuera, Ramon (Array, 2012)
Objective Exposure to war can negatively affect health and may impact on healthcare costs. Estimating these costs and identifying their predictors is important for appropriate service planning. We aimed to measure use of health services in an adult population who had experienced war in the former-Yugoslavia on average 8 years previously, and to identify characteristics associated with the use and costs of healthcare. Method War-affected community samples in Bosnia-Herzegovina, Croatia, Kosovo, FYR Macedonia, and Serbia were recruited through a random walk technique. Refugees in Germany, Italy and the UK were contacted through registers, organisations and networking. Current service use was measured for the previous three months and combined with unit costs for each country for the year 2006/7. A two-part approach was used, to identify predictors of service use with a multiple logistic regression model and predictors of cost with a generalised linear regression model. Results 3, 313 participants were interviewed in Balkan countries and 854 refugees in Western European countries. In the Balkan countries, traumatic events and mental health status were related to greater service use while in Western countries these associations were not found. Participants in Balkan countries with post traumatic stress disorder (PTSD) had costs that were 63% higher (p = 0.005) than those without PTSD. Distress experienced during the most traumatic war event was associated with higher costs (p = 0.013). In Western European countries costs were 76% higher if non-PTSD anxiety disorders were present (0.027) and 63% higher for mood disorders (p = 0.006). Conclusions War experiences and their effects on mental health are associated with increased health care costs even many years later, especially for those who stayed in the area of conflict. Focussing on the mental health impact of war is important for many reasons including those of an economic nature.